Connecting Status and Professional Learning: An Analysis of Midwives Career Using the Place© Model - Patricia Gillen (MDPI AG, 2019)
This paper seeks to deconstruct the place of midwives as professionals using the novel interdisciplinary lens of the Place Model-an innovative analytical device which originated in education and has been previously applied to both teachers and teacher educators. The Place Model allows us to map the metaphorical professional landscape of the midwife and to consider how and where midwives are located in the combined context of two senses of place: in the sociological sense of public esteem and also the humanistic geography tradition of place as a cumulative process of professional learning. A range of exemplars will bring this map to life uncovering both the dystopias and potentially utopian places in which midwives find their various professional places in the world. The Model can be used to help student midwives to consider and take charge of their learning and status trajectories within the profession.